THE ROLE OF SHARIA E-MONEY IN TRANSACTIONS OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Sukiman Sukiman; Sugianto Sugianto; Darwin Darwin (Proceeding International Seminar of Islamic Studies, 2022)
This research is a literature study that discusses the role of Sharia E-Money in Transactions of Micro, Small and Medium Enterprises (MSMEs). Referring to some of the literature that has been discussed previously, it is concluded that Islamic sharia principles through non-cash transactions (e-money) play an important role in moving the wheels of the Indonesian economy through the development and empowerment of MSMEs. Where it can make it easier for users to make transactions, so as to be able to strengthen MSMEs in an Islamic economic perspective by implementing non-cash payments (e-money) this has a positive impact on both MSME actors and users because it can help save expenses and also increase income. In addition, the Indonesian people, whose majority are Muslims, Of course this is a big opportunity in the development of a sharia-based economy in Indonesia. Because sharia e-money is not limited to Muslim users, it can also be used for non-Muslim people. In the end, the development of sharia e-money will increase the convenience of the public in financial transactions.Keywords: Transactions, Actors, MSMEs, E-Money, Sharia